What If Your Husband Doesn’t Feel the Pressure? An Exploration of Women’s Involvement in WaSH Decision Making in Nyanchwa, Kenya - Abu, Thelma Zulfawu (Int J Environ Res Public Health, 2019)
Access to water, sanitation and hygiene (WaSH) is a major challenge in sub-Saharan Africa (SSA). Women and girls suffer the main burden of a lack of access to WaSH because they are primarily responsible for collecting water for their homes. However, they are often excluded from WaSH decision-making and implementation processes. This research sought to explore women’s experiences in participating in WaSH decision-making through a case study in Nyanchwa, Kenya. Twelve (12) key informant interviews were conducted with community leaders and members regarding challenges and possible measures for enhancing women and girls’ participation in WaSH decision-making. From this research, it is evident that economic challenges and cultural factors such as male dominance, greatly inhibit women and girls’ participation in WaSH decision-making and implementation processes. Other factors such as time constraints and low literacy rates also emerged. The paper concludes with a call for collaboration among women’s groups to enhance collective action for improved access to WaSH. This will undoubtedly lead to enhanced community health and wellbeing (Sustainable Development Goal 3, SDG3) through the empowerment of women (Sustainable Development Goal 5, SDG5).